2019
DOI: 10.1016/j.ejvs.2019.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Long-term Follow Up After Endovascular Abdominal Aortic Aneurysm Repair With the Zenith Stent Graft

Abstract: This paper reports the 16 year outcomes of elective endovascular aneurysm repair (EVAR) with the Zenith stent graft. The results indicate that graft related complications keep appearing years after the primary procedure, suggesting mandatory lifelong surveillance. Abdominal aortic aneurysm rupture is rare after EVAR, with a mean annual risk of 0.5%, and is not prevented by regular follow up.Objective/Background: Although endovascular aneurysm repair (EVAR) has been widely adopted, long-term data remain limited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
24
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 27 publications
0
24
2
Order By: Relevance
“…The low 1.4% rate of aneurysm-related mortality would be expected in patients who fulfill the anatomical criteria for EVAR and are relatively free from aneurysm-related complications and secondary interventions. Vaaramaki et al 27 recently reported long-term follow-up of patients treated with the Zenith stent-graft. Ten patients (3.5%) experienced rupture after EVAR, 7 of them due to type I endoleak during a mean follow-up of 76 months.…”
Section: Discussionmentioning
confidence: 99%
“…The low 1.4% rate of aneurysm-related mortality would be expected in patients who fulfill the anatomical criteria for EVAR and are relatively free from aneurysm-related complications and secondary interventions. Vaaramaki et al 27 recently reported long-term follow-up of patients treated with the Zenith stent-graft. Ten patients (3.5%) experienced rupture after EVAR, 7 of them due to type I endoleak during a mean follow-up of 76 months.…”
Section: Discussionmentioning
confidence: 99%
“…After this period the need for secondary interventions continues to remain stable over time similar to other long-term studies. 24,25 The majority of patients with an abnormal CTA that underwent a secondary intervention were asymptomatic and underwent their first intervention due to surveillance imaging after EVAR. A smaller proportion presented with symptoms, all of whom needed secondary intervention.…”
Section: Discussionmentioning
confidence: 99%
“…2 days C. 3 days D. 5 days E. 7 days 2. The re-intervention rate at ten years after endovascular aneurysm repair (EVAR) with the Zenith stent graft is 2 A. 7% B.…”
mentioning
confidence: 99%